Identification of Vibrio parahaemolyticus Isolates by PCR Targeted to the toxR Gene - Elamparithi, P. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Vibrio parahaemolyticus is a major cause of food borne illness such as gastroenteritis in human through consumption of undercooked seafood or wounds exposed to marine animals or warm coastal waters especially in Southeast Asian. This is because a short warm period is sufficient for Vibrio parahaemolyticus which has short generation time to grow until infectious levels (106 organisms). There are many methods used in the detection of Vibrio parahaemolyticus. The standard selective medium method used for Vibrio is Thiosulfate citrate bile salt sucrose agar (TCBS). Vibrio parahaemolyticus colonies are green or blue green on the agar due to sucrose fermentation. The latest technique would be PCR that can be used for detection of Vibrio parahaemolyticus in various samples including seafoods or other samples, and this method is faster, easier and more reliable. This technique can be applied because of the presence of toxR gene that appears to be well conserved among Vibrio parahaemolyticus. This gene can be used to develop a PCR method for identification of Vibrio parahaemolyticus. In this study, the fish sample (Sangara– Red snapper, Lutjanus compechanus) was collected from costal belt of Cuddalore district. When the sample was streaked on the TCBS agar, Green colour Vibrio parahaemolyticus colony was observed and was they were grown on selective medium, TCBS agar. Specific-PCR for toxR gene detection gave positive result in which a band with 368 bp size appeared on gel confirmed the presence of Vibrio parahaemolyticus.